Analysis of Non-Equal Marriage Practices in Ammatoa Customary Law and the Pasang ri Kajang Tradition from an Islamic Law Perspective - Fatimah, Nurul; Amin, Muhammadiyah; Ilham, Muh. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The main issue in this study is â€œAnalysis of Non-Equal Marriage Practices in Ammatoa Customary Law and the Pasang ri Kajang Tradition from an Islamic Law Perspective.â€ This research aims to provide an overview of the practice of non-equal marriages in the Ammatoa customary area, analyze the impact of non-equal marriage practices on the Ammatoa Kajang community, and elaborate the Islamic legal perspective on customary rules regarding non-equal marriage within the Ammatoa society. This study is qualitative (field research) with an ethnographic focus on the Pasang ri Kajang tradition, employing normative juridical, sociological, and anthropological approaches. Data sources were obtained from customary leaders, community members, the village head of Bontoharu, youth leaders, customary officials, religious leaders, the Bulukumba Ulama Council, Nahdlatul Ulama Bulukumba, and academicians. Data collection methods included observation, interviews, and documentation. Data processing and analysis were conducted through data editing, data reduction, data presentation, comparative analysis, and drawing conclusions. The results show that the practice of non-equal marriage according to the Pasang ri Kajang tradition is permissible when the male party belongs to the puang (noble) class and the female party belongs to the ata (commoner) class. Conversely, marriages between women from the puang class and men from the ata class are prohibited, as they are considered contrary to prevailing customary law. This practice contributes to discriminatory treatment against the ata class, both socially and within the customary legal system, leading to psychological pressure, limited social space, and the non-fulfillment of equality before the law.